When are auctions best? - Bulow, Jeremy; Klemperer, Paul 1956- (Working paper series / National Bureau of Economic Research, 2007)
We compare the two most common bidding processes for selling a company or other asset when participation is costly to buyers. In an auction all entry decisions are made prior to any bidding. In a sequential bidding process earlier entrants can make bids before later entrants choose whether to compete. The sequential process is more efficient because entrants base their decisions on superior information. But pre-emptive bids transfer surplus from the seller to buyers. Because the auction is more conducive to entry in several ways it usually generates higher expected revenue.